A device for functional and cosmetic improvement of lagophtalmos due to facial paralysis - Aşık, Mehmet Doğan. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2009., 2009)
A new device for the correction of eyelid problems due to facial palsy was studied. Lagophthalmos is the condition of the paralyzed eyelids' to close totally. It may cause drying and irritation .In this thesis, 14 rabbits were injected with local anaesthetics to induce temporary facial palsy and lagophtalmos. In order to provide functionality to the upper eyelids, ferromagnetic steel pieces were placed inside and outside of the eyelids of the rabbits. The device moves the eyelids by magnetically pulling the steel pieces. The control group (n=5) did not wear the device.The treatment group with external implant (n=4) and the treatment group with internal implant (n=5) made to wear device and tested. All animals were observed during the experiments and recorded to video tapes. The data collected from video records were analyzed to test the statistical di erence between control and the treated groups. The results showed that treatment groups paralyzed eye and control groups paralyzed eye have signi cant di erences. Furthermore, the treatment group with internal implant shows a noticeable similarity with the healthy(un-paralyzed) eye.|Keywords: Lagophtalmos, Facial Palsy, Implant, Medical Device, Rabbit.
Keywords: Facial paralysis.; Implants, Artificial.